Isolation of GSH from Baker Yeast by Ultrasonic method - Mohamed Salleh, Mohamad Ramlan; Jamal, Parveen; Salleh, Rohani; Hasim, Haslinda (Asian Network for Scientific Information, 2004)
The purpose of this study was to determine the effect of operating parameters such as the yeast concentration, processing temperature and isolation time on the isolation of GSH using Ultrasonic method. The disrupted cells solution was centrifuged at 12,000 rpm for 20 min and the GSH content in the supernatant was analyzed by taking the OD value of the solution using Spectrophotometer at 412 nm. To study the effect of yeast concentration, yeast solution with the concentration of 3, 6, 9 and 12 wt.% was disrupted at their original temperature for 15 sec. The result shows that the optimum value of yeast concentration is 6 wt.% where 12.93 μmol mL-1 GSH was isolated. To study the effect of processing temperature, Ultrasonic process of the 6 wt.% yeast solution was done at various values of temperature such as 19, 22, 25, 28, 30 and 40C for 15 sec. The results indicated that, the optimum GSH isolation temperature is 22C with the isolation of 13.53 μmol mL-1 GSH. Then, to study the effect of isolation time, the Ultrasonic process of sample with the concentration of 6 wt.% was done at 22C for 15, 30, 45 and 60 sec. The result indicated that the optimum isolation time for the Ultrasonic process is 15 sec.